Hydrate growth at the interface between water and pure or mixed CO2/CH4 gases: Influence of pressure, temperature, gas composition and water-soluble surfactants. (18th August 2015) - Daniel-David, Delphine; Guerton, Fabrice; Dicharry, Christophe; Torré, Jean-Philippe; Broseta, Daniel
Abstract: The morphology and growth of gas hydrate at the interface between an aqueous solution and gaseous mixtures of CO2 and CH4 are observed by means of a simple experimental procedure, in which hydrate formation is triggered at the top of a sessile water drop by contact with another piece of gas hydrate and the ensuing hydrate growth is video-monitored. The aqueous solution is either pure water or a solution of a nonionic or anionic surfactant at low concentration (in the 100–1000 ppmw range). In agreement with previously published data, hydrates formed from pure water and aqueous solutions of non-ionic surfactant grow rapidly as a low-permeable polycrystalline crust along the water/gas interface, which then inhibits further growth in a direction perpendicular to the interface. Lateral growth rates increase strongly with subcooling and CO2 content in the gas mixture. Similar lateral growth rates, but varying morphologies, are observed with the non-ionic surfactants tested. In contrast, the two anionic surfactants tested, sodium dodecyl sulfate (SDS) and dioctyl sodium sulfosuccinate (AOT), promote in the presence of CH4 (but not in the presence of CO2 ) a rapid and full conversion of the water drop into hydrate through a 'capillary-driven' growth process. Insights are given into this process, which is observed with AOT for an unprecedented low concentration of 100 ppmw. Highlights: Hydrate growth is observed from experiments with water drops and CH4 /CO2 gases. Hydrates most often form low-permeable crusts at water/gas interfaces. Anionic surfactants such as SDS or AOT promote CH4 hydrates but not CO2 hydrates. Insight is given into the capillary-driven hydrate growth observed with SDS and AOT.